Expanding research capacity and accelerating AIDS vaccine development in Asia - Jean Louis Excler (2018)
According to the Joint UN Program on AIDS (UNAIDS), an estimated 4.9 million adults and children are living with HIV in Asia and the Pacific. Refinement and development of existing and new prevention and treatment technologies - including safe, effective, and accessible AIDS vaccines - are urgent public health priorities. The Asian region faces several challenges for AIDS vaccine development. There are multiple genetic variants of HIV-1 driving the epidemic in the region and too few vaccine candidates in the pipeline targeting those subtypes. Low HIV incidence throughout the region means that trial sites must recruit larger numbers of volunteers and shift their focus to higher-risk populations where incidence is higher. Also, the cultural, economic, and political diversity of the region may render collaboration very complex, but also beneficial at a regional level. Recognizing that collaborating as a region could foster and accelerate AIDS vaccine development, participants at the Sapporo International Consultation recommended that an AIDS Vaccine Asian Network (AVAN) be created to facilitate interactions between donors and funding opportunities, increase regional clinical trial and production capacity, support region-specific advocacy and communication strategies, contribute to the Global HIV Vaccine Enterprise Scientific Plan, prepare a regional approach for future vaccine deployment, and develop a regional platform for clinical trials including harmonized legal, regulatory, and ethical frameworks.